2014
DOI: 10.1371/journal.pone.0115770
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Protein C Receptor Gene Variants Not Associated with Severe Malaria in Ghanaian Children

Abstract: BackgroundTwo recent reports have identified the Endothelial Protein C Receptor (EPCR) as a key molecule implicated in severe malaria pathology. First, it was shown that EPCR in the human microvasculature mediates sequestration of Plasmodium falciparum-infected erythrocytes. Second, microvascular thrombosis, one of the major processes causing cerebral malaria, was linked to a reduction in EPCR expression in cerebral endothelial layers. It was speculated that genetic variation affecting EPCR functionality could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…This vicious cycle, involving reducing the interaction between mEPCR and PC to promote pro‐inflammatory cytokine production, may aggravate the severity of malaria. At the genetic level, no association between any of the genotypes and disease phenotype was observed (Table ), confirming earlier studies .…”
Section: Discussionsupporting
confidence: 89%
“…This vicious cycle, involving reducing the interaction between mEPCR and PC to promote pro‐inflammatory cytokine production, may aggravate the severity of malaria. At the genetic level, no association between any of the genotypes and disease phenotype was observed (Table ), confirming earlier studies .…”
Section: Discussionsupporting
confidence: 89%
“…For example, a large Ghanaian association study failed to link EPCR H3 haplotype with malaria disease severity. 104 In contrast, a recent Thai study found that elevated sEPCR plasma levels in individuals with H3 haplotype were associated with protection from CM. 105 Evidently, larger studies are required to unequivocally determine whether EPCR haplotype and constitutively high sEPCR plasma concentration truly have an effect on malaria disease severity.…”
Section: Attenuation Of Anticoagulation Pathwaysmentioning
confidence: 88%
“…1). Five studies, published from 2014 to 2016, were eligible for meta-analysis [1,2,[24][25][26]. A total of 2995 SM, 487 uncomplicated malaria, and 2105 healthy controls from Thailand, Uganda, Benin, Tanzania, and Ghana were enrolled.…”
Section: Identification Of Relevant Studies and Study Characteristicsmentioning
confidence: 99%
“…The abundance of the transcripts increased with malaria severity; however, each subtype transcript did not vary remarkedly among patients, which suggests that all EPCR-binding CIDRα1 subtypes are required to be targeted to deplete P. falciparum sequestration in host blood circulation, in particular for sequestration in brain blood circulation [11]. Several lines of evidence support a correlation between the plasma EPCR (soluble EPCR, sEPCR) levels and the genetic polymorphisms of the EPCR gene, particularly the EPCR rs867186-A/G genotype [1,2,[24][25][26]. sEPCR can competitively bind to the CIDRα1 domain and therefore displaces EPCR binding sites for APC, which restores cellular EPCR function.…”
Section: Introductionmentioning
confidence: 99%